Green marketing innovation and sustainable consumption: A bibliometric analysis. (10th August 2022) - Kumar Kar, Sanjay; Harichandan, Sidhartha
Abstract: This comprehensive analysis of 1121 research and review articles published in 462 journals listed in the Scopus and Web of Science databases during 1990–2021 provides measurable and meaningful insights into research trends in sustainable consumption and green marketing innovation. Results confirm that the literature on the above field has been on the rise, particularly since 2015. The average publication per year is 4.11 and the average citation per document is 32. So far, 2628 authors from 66 countries have been contributing to the sustainable consumption and green marketing innovation research. China is the leader with 214 publications followed by Spain (76), and USA (62). Our analysis shows aspects like eco-tourism, sustainable and innovative marketing techniques, and green labelling are increasingly getting importance. Further, areas that require future research include waste material disposal, green product certification, and aggregating sustainable purchases across product categories. Therefore, international cooperation and collaboration among nations and research institutions should be advanced with a special focus on designing innovative green marketing techniques to foster sustainable consumerism.